The Court Mechanism in the Election Organization Ethics Council (DKPP) within the Context of Constitutional Law - Febriant, Achmad Reynaldi; Suartini, Suartini; Hidayat, Yusuf (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
The Role of the Election Organization Ethics Council's (DKPP) in Elections and Constitutional Law was established in response to frequent ethical violations by election organizers. This research aims to gain a deep understanding of the process of conducting ethical hearings for election organizers and to explain human rights in providing testimony during DKPP hearings. Additionally, this study analyzes the proof process in DKPP to determine whether it adheres to the applicable laws and regulations. The research methodology used is normative juridical legal research, which combines a legislative approach with a conceptual approach. The legislative approach involves the analysis of various applicable legal rules, while the conceptual approach focuses on the understanding and application of relevant legal concepts in this context.